Exosomal lncRNA XR_001793654.1 in human cardiac explant-derived alleviates atrial fibrillation via abolishing the miR-107-3p-mediated KLF13 inhibition - Liang, Yanxiao; Li, Dongyu; Wang, Huishan; Tian, Yuan (Frontiers in Cell and Developmental Biology, 2025)
BackgroundAtrial fibrillation (AF) is a type of arrhythmia that occurs in the upper part of the heart. Extracellular vesicles (EVs) released by human cardiac explant-derived cells (CDCs) contain bioactive cargos that may function as diagnostic indicators or therapeutic candidates for AF. The lncRNA XR_001793654.1 has been identified as a putative modulator in AF pathogenesis.MethodsHuman CDCs were derived from left atrial appendages collected during cardiac surgery. Then, EVs were isolated from cultured CDCs using ultracentrifugation. XR_001793654.1 expression was quantified in EVs. The relationship between XR_001793654.1, miR-107-3p, and KLF13 was identified.ResultsXR_001793654.1 was upregulated in EVs from human CDCs. Systemic delivery of these EVs in vivo diminished atrial fibrosis and hypertrophy, with concurrent suppression of inflammatory cell accumulation and pro-inflammatory cytokine release. Mechanistically, EV-associated XR_001793654.1 served as ceRNA, sequestering miR-107-3p and thereby alleviating its inhibitory regulation of KLF13 expression. Elevation of KLF13 was essential for the observed cardioprotective outcomes.ConclusionIn conclusion, human CDC-derived EV containing XR_001793654.1 alleviates atrial fibrosis and AF through neutralizing miR-107-3p-mediated downregulation of KLF13. These findings offer new perspectives on AF molecular mechanisms and emphasize XR_001793654.1 as a promising intervention target.